Predictors of perceptions of human rights violations during the Chilean social outburst of 2019 - Carrasco Paillamilla, Silvia F.; Disi Pavlic, Rodolfo (Frontiers in Psychology, 2023)
The 2019 social outburst was a watershed moment for Chilean politics and society. One of its defining features was the scale and severeness of human rights violations committed by the armed forces and the Police during the demonstrations and riots, which were reported by various independent and international sources. Few works, however, have systematically analyzed perceptions of human rights violations in this type of contentious context. Using data from a nationally representative survey fielded during the unrest, we identify the correlates of perceptions of human rights violations during the outburst through ordered logistic regressions. We find that participation in demonstrations, use of social media for political information, fear of crime and proximity to violent protests are correlated with the perception that security forces violated human rights frequently during the outburst.